A deposition strategy for Wire Arc Additive Manufacturing based on temperature variance analysis to minimize overflow and distortion. (6th January 2023) - Alhakeem, Mohammad Mazen; Mollamahmutoglu, Mehmet; Yilmaz, Oguzhan; Bol, Nevzat; Kara, Ozge Ece
Abstract: Wire Arc Additive Manufacturing method allows producing relatively large metal parts with minimum raw material. However, the high heat input used during production results in heat accumulation and temperature variance. Both of them can cause various problems, such as distortion, overflow, and residual stress. Heat accumulation is the rise in temperature that occurs as a result of the inability to remove heat from the part. On the other hand, temperature variance arises as a result of the deposition path planning, which is usually carried out according to the geometrical shape of the part section. In traditional deposition path planning approaches, temperature variance is not taken into account for two reasons: high computational cost and the need to use more than one tool to implement path planning and thermal analysis. In this study, an algorithm that plans deposition paths by one step via performing thermal analysis to minimize temperature variance on a path basis is presented. The algorithm determines the deposition path by finding the best deposition angle and the sequence of tracks according to the jumping to the coldest deposition area. Thus, the temperature variance is reduced significantly. To evaluate the algorithm performance, a part consisting of a bulk component and a thin-walled component was produced in the workshop using the proposed algorithm and traditional sequential raster strategy. The results showed that the developed strategy reduced surface deformation by 37 % and thin-walled overflow by 21 %. Highlights: A deposition path planning algorithm based on thermal analysis for Wire Arc Additive Manufacturing Temperature variance analysis to reduce the overflow and distortion An efficient thermal model for thermal-based deposition path planning